The Importance of Improving the Business Environment in Promoting the Competiveness of the Tourism Sector in Algeria: A Comparative Study with a Group of Arab Countries - Kelleche, Abdellah; Khantar, Nawal (The Arab Journal of Administration, 2021)
Our aim is to analize the need to improve the business environment in order to enhance the competitiveness of the tourism sector in Algeria. For this reason, we analyzed the competitiveness of the tourism sector in Algeria compared to the Arab countries according to the report of the competitiveness of tourism and travel issued by the world economic forum 2017, which is composed of four sub-indicators; which are in the enabling environment, which are also divided into sub-indices: business environment, safety and security, health and hygiene, human resources and labor market, ict readiness and the policy and empowerment policy index, international openness, price competitiveness, environmental sustainability, and the third indicator is the infrastructure which is the air transport environment, the infrastructure of the land and the port, the infrastructure of tourism services, while the last indicator of natural and cultural resources wz analyze the situation of private and public environmental factors that affect the competitiveness of the tourism sector in Algeria and its contribution to that in comparison to a group of Arab countries. Finally, we reach the most important approaches which may be used in reforming the Algerian business environment. Based on an analysis of factors impeding the development process, and assess the efforts and reforms adopted by States in this area, organizational, legislative and institutional aspects and to evaluate the results achieved on the ground we found that the latter was not in the level of aspirations, it did not reflect the magnitude of the financial, human and regulatory burdens adopted by the State compared to the performance of the tourism sector in the Arab countries adopted in this study ,This is despite the availability The ingredients Cultural, historical and natural Necessary for the recovery of the tourism sector, This led us to conclude that the lack of performance of the tourism sector in Algeria is mainly due to negative factors that characterize the administrative, organizational, social and cultural system, which greatly encourage the spread of the phenomenon of administrative corruption of all kinds, in addition to the culture of consumption and reliance on rents, This requires radical reforms, in addition to the administrative and organizational aspects, Social and cultural aspects, with the aim of instilling values that will help develop the tourism sector.